The Physical Development and Physical Preparedness of the Students at the Age of 17-20 Years Old Who Go in for Track and Field - D. O. Abdyrakhmanova,; Dzhanuzakov K. Ch., (Journal of Educational Issues, 2024)
The impact of regular track and field trainings on student’s physical development and physical preparedness have been studied in the work. The study was conducted in the Kyrgyz-Turkish Manas University. İn total, 64 students at the age of 17-20 years have participated into the study. Applied methods: anthropometry, physiometry, the Stange-Hench tests. Sports and pedagogical control tests (on flexibility, strength, speed, endurance and agility) have been used as well. While evaluating students’ physical development, the second study of both ‘Sports’ and ‘Initial’ groups has revealed the high indices among boys according to the following criteria: body height and weight, chest bulk, vital capacity, chest excursion and the Stange-Hench tests. According to the heart rate criterion, the indices of the “Sports” group were reliably higher than those of the “Initial” group (P < 0.05). During the comparison of the second study results of girls’ physical development, more reliable distinctions have been found out (P < 0.05). When the physical development indices were under the study, the second examination exposed and proved that the flexibility of boys from ‘Sports’ group being higher on 7.1 cm (P < 0.05). The experimental materials provided in this article gave an opportunity for concluding that systematic track and field trainings had had a positive impact on the physical development indices, to be precise on the functional condition and physical preparedness level of boys and girls at the age 17-20 years old.